Concrete a material for sustainable construction - Gonçalves, A. (2013)
The growth of human population, primarily on urban areas, and the corresponding increase of social needs have a large impact in the development of the construction sector. Being aware of these challenges the construction industry attempts to plan for the future by taking into account the environmental, the economic and the social issues throughout the total lifecycle of materials, i. e., using a sustainable methodology. In what concerns to construction and building materials a special highlight to concrete must be given. As it is known, concrete structures may stand for a long time with minimal maintenance and allow energy savings through its lifetime when compared to other building materials. These aspects contributed to the predominant use of concrete with high environmental impacts associated. To reverse this situation the concrete industry is making improvements that include the use of supplementary cementitious materials and alternative aggregates and the development of new binders with lower greenhouse gas emissions. Within the European framework of sustainability of construction works the assessment of construction materials sustainability requires an Environmental Product Declaration (EPD) which includes information about the environmental impacts associated with its using specific rules that ensure a consistent evaluation of a particular product, Product Category Rules (PCR). For concrete the European Committee for Standardization (CEN) is developing PCR for all concretes covered by EN 206. The establishment of a declared unit, the reference service life and the life cycle stages covered are the main points under discussion. In this communication the above issues are addressed pointing out the difficulties on weighing indicators and decision-making.